Adenosine deaminase promotes goose astrovirus genotype II replication in GEF cells - Saimin Zhai; Ruixue Li; Keying Liu; Huichao Gao; Xia Yang; Jun Zhao; Xiaozhan Zhang; Zeng Wang (Poultry Science)
Goose astrovirus genotype II (GAstV-II), the causative agent of visceral and joint gout in goslings, has been widespread in China since 2016 and resulted in considerable economic losses to waterfowl industry. As an important enzyme involved in purine metabolism and uricogenesis, adenosine deaminase (ADA) is reported to be upregulated via GAstV infection. However, knowledge about the regulatory role of ADA played during virus replication is still limited. In the present work, goose ADA (gADA) was firstly cloned from goose embryo fibroblasts (GEF) and phylogenetic analysis showed that it was highly homologous with duck ADA, sharing 96.6 % identity in nucleotide sequences. Moreover, GAstV-II infection promoted the production of gADA but did not change its cellular distribution pattern, which was evenly dispersed in the cytoplasm and nucleus. Further results demonstrated that ectopic expression of gADA significantly enhanced viral capsid protein expression and virus loads in GEF cells. Conversely, knockdown of gADA by siRNA played the opposite role in virus replication. Notably, gADA could directly interact with viral capsid protein, particularly with its C-terminal domain. Our data elucidated the regulatory role of gADA during GAstV-II infection, thereby laying a solid foundation to further explore its pathogenesis.